Housing Reconstruction in Urban and Rural Areas - Trohanis, Zoe; Read, Geoffrey (2012)
The destructive Wenchuan earthquake of magnitude 8.0 occurred at 2:28 pm local time on 12 May 2008, in the western Sichuan province of China. The reconstruction of public and private housing emerged as a key issue for the Government of China. This note discusses delivery mechanisms and financing strategies for housing reconstruction, as well as gives examples of recent international experience with post-disaster housing reconstruction programs and key issues for consideration by the government moving forward.